THE IMPACT OF ACCOUNTING RECORDS MANAGEMENT ON THE FINANCIAL PERFORMANCE OF A BUSINESS. - Nansubuga Rebecca (Uganda Christian University, 2024)
The study investigates the impact of accounting records management on the financial performance of a business with concern on Buy More Supermarket in Kirinya, Wakiso district. The main objective of the study was to examine the overall impact of records management on the financial performance of businesses, a case of Buy More Supermarket and other objectives were to examine the degree to which effective records management influences operational efficiency, to find out whether accessibility to records contributes to informed financial decision-making and to find out whether effective records management influences cost reduction in businesses. The emphasized businesses especially small-scale to embrace records management as it is vital in the administration of business activities. The independent variables were operational efficiency, cost reduction, and informed financial decision-making. The dependent variables were profitability and new product line. This literature reviewed other existing data about the same study topic. Mainly primary data was used in coming up with the work and partly secondary. The methods of data collection used were questionnaires, interviews, and document reviews. The instruments used in data collection were a questionnaire guide and an interview guide. The results of the study showed that majority of respondents agreed that records management is vital in the administration of the business. The researcher concluded the study, recommendations, limitations and areas for further studies.